Three renowned artists join gallery lineup (Raton, NM Raton Range, 1994)
This article is about three new artist joining the gallery.
Newspaper article
Master list item #: 52
File location is in the Raton file Cabinet
Keywords: Franco, Manuel -- Artist; Sullivan, Emmett -- Artist; Hollebeke, Karin -- Artist; Gibat, M. J. -- Jeweler; Sun Spirit Baskets; Old Pass Gallery; Art Displays; Local Artist; Art Sales; Raton, New Mexico